First record of the root knot nematode, Meloidogyne minor in New Zealand with description, sequencing information and key to known species of Meloidogyne in New Zealand - Zhao, Zeng Qi; Ho, Wellcome; Griffin, Ruth; Surrey, Michael; Taylor, Robert; Aalders, Lee T.; Bell, Nigel L.; Xu, Yu Mei; Alexander, Brett J. R. (Zootaxa, 2017)
Meloidogyne minor Karssen et al. 2004 was collected from perennial ryegrass (Lolium perenne L.) growing in a sports ground in Christchurch, New Zealand. This is a new record for M. minor, the first report of this nematode occurring in New Zealand, and the second report from the southern hemisphere (after Chile). In general, the New Zealand isolate of M. minor corresponds well to the descriptions of M. minor given by Karssen et al. (2004). The New Zealand isolate is characterized by having a female with dorsally curved stylet, 13–14 μm long, with transversely ovoid knobs slightly sloping backwards from shaft; rounded perineal pattern; and male with stylet 16–19 μm long, large transversely ovoid knobs sloping slightly backwards from shaft; head region not set off, labial disc elevated, lateral lips prominent; and second stage juvenile 370–390 μm long, with hemizonid posterior but adjacent to excretory pore; tail 53–63 μm long; and a distinct hyaline tail terminus 14–18 μm long. In addition, molecular phylogeny using near full length small subunit (SSU), D2/D3 expansion segments of the large subunit (LSU), the internal transcribed spacer region (ITS1 and 2), and the intergenic spacer (IGS2) of the ribosomal rDNA supports the identification.